Neighborhood effects on dietary behaviors—evidence from older adults in China - Liu, Chang; Yu, Hao (Frontiers in Nutrition, 2022)
Individual neighborhood environment is an important predictor of dietary behavior. Using data from four waves of the China Health and Nutrition Survey (CHNS, 2004–2011), this study applied a panel data approach to examine the effects of neighborhood diet quality on the eating behaviors of older adults living in the same community. Results of the fixed effects estimation indicated a significant neighborhood effect within the community, and neighborhoods with high-quality diets had a significantly positive effect on the eating behavior of the elderly. The neighborhood effects on elderly eating behaviors were manifested in improved dietary structure, including decreased consumption of cereals and increased consumption of vegetables and fruits, as well as meat, eggs, and dairy products. In terms of nutrient intake, there was a significant increase in protein intake, and hence, a greater percentage of calories from protein. The estimation results were robust when different estimation methods or diet quality measures were used. Future policies for improving diet quality should consider neighborhood-level conditions, especially in rural areas where residents are closely connected and socially interact with one another.